(untitled) (Journal of Forensic Medicine & Toxicology, 2016)
Suicide note also known as death note is message left by someone who commits suicide or who intends to commit suicide. It is the closest and the final word which get to the suicidal mind before death. Due importance should be given at the site of crime for recovery of suicide note as it is an important piece of evidence showing psyche of the patient and plays an important role in understanding reasons of suicide. Due to scarcity of data on the study of suicide note the present article is an effort to evaluate the psychology of victim in suicide notes with respect to mode of writing, to whom it is addressed and victim’s last wish. The suicide and can be simple or complex. The complex notes may have contents of abetment , mental illness , abuse , torture etc., which may require further investigation. In this study only a small number of 21 suicide notes were studied and majority were simple and straight. The larger number of suicide notes and multicentre studies are required to have psychological insight and reasons of the person committing suicide. The will aim towards to bring some help to prevention of suicides programme.